Musicians in the marsh: a new species of music frog (Anura: Ranidae: Nidirana) from Arunachal Pradesh, India - Boruah, Bitupan; Deepak, V.; Das, Abhijit (Zootaxa, 2023)
We describe a new species of ranid frog of the genus Nidirana from northeast India based on morphological, molecular and acoustic evidence. The new species is phenotypically distinct from its congeners by a combination of morphological characters: body robust with SVL 46.5–59.1 mm (n= 3) in adult males and SVL 60.6–66.0 mm (n= 2) in adult females; a pair of subgular vocal sacs and two patches of nuptial pad on the first finger in adult males; toe tips slightly dilated and oval; circum-marginal grooves present on all toes; dorsal skin with scattered small tubercles. A pale cream-coloured mid-dorsal line from the snout tip to the vent is present. Phylogenetically, the new species differs from its congeners by a genetic divergence of 3.4–8.0% and 7.7–12.4% in 16S and COI genes respectively. Furthermore, the new species can be differentiated from its congeners by its advertisement call, which consists of two different types of notes, call duration (0.58–0.92 s) and dominant frequency of the call (473.7 Hz). The discovery of a new species validates the presence of the genus Nidirana from India and emphasizes the importance of exploring specialized habitats such as marshlands, which are often overlooked.